2009
DOI: 10.1186/1757-1626-2-190
|View full text |Cite
|
Sign up to set email alerts
|

Gluteal compartment syndrome: a case report

Abstract: IntroductionGluteal compartment syndrome is a rare, often unrecognized syndrome that may manifest as renal failure, sepsis, and death. Delay in diagnosis can result in significant morbidity and possible mortality. We report a case of occult gluteal compartment syndrome causing unresolving rhabdomyolysis.Case PresentationA 50-year-old Caucasian American man with history of chronic obstructive pulmonary disease was admitted status post fall and loss of consciousness for an unknown duration. Initial work-up revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 5 publications
2
25
0
Order By: Relevance
“…Examination will reveal worsening of the pain during passive movement of the hip, notably flexion and adduction, with weak active extension and abduction. Additional features suggesting compartment syndrome may include skin erythema or bruising, tense swelling of the buttocks and paraesthesia along the distribution of the sciatic nerve 5. As in our patient, moderate pain persisted after decompression of the gluteus maximus necessitating an epidural postoperatively.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Examination will reveal worsening of the pain during passive movement of the hip, notably flexion and adduction, with weak active extension and abduction. Additional features suggesting compartment syndrome may include skin erythema or bruising, tense swelling of the buttocks and paraesthesia along the distribution of the sciatic nerve 5. As in our patient, moderate pain persisted after decompression of the gluteus maximus necessitating an epidural postoperatively.…”
Section: Discussionsupporting
confidence: 53%
“…Within the gluteal region, three fascial compartments exist5: (1) the gluteus maximus; (2) gluteus medius/minimus and (3) the tensor fascia lata. Each of these is held within its own fascial space.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our case and review of the literature, gluteal compartment syndrome must be considered as a serious complication of pelvic trauma, which might lead to fatal outcome [1][2][3][6][7][8][9][10]. The main stage of the treatment relates to prompt diagnosis and early surgery [10].…”
Section: Discussionmentioning
confidence: 99%
“…There are three distinct gluteal compartments: gluteus maximus, gluteus medius and minimus, and tensor fascia latae 12 13. The release of all these compartments is vital in the treatment of compartment syndrome in the gluteal region.…”
Section: Discussionmentioning
confidence: 99%
“…The release of all these compartments is vital in the treatment of compartment syndrome in the gluteal region. Studies have shown that ischaemia of 4 h duration can cause irretrievable muscle damage 12 14. This case shows that permanent muscle ischaemia (ie, muscle death) can occur before this allotted timeline and this in our case, was due to the high tamponading pressures caused by the arterial bleed.…”
Section: Discussionmentioning
confidence: 99%